2022
DOI: 10.1126/sciadv.abm3470
|View full text |Cite
|
Sign up to set email alerts
|

Tet-mediated DNA demethylation regulates specification of hematopoietic stem and progenitor cells during mammalian embryogenesis

Abstract: Ten-eleven translocation (Tet) enzymes promote DNA demethylation by oxidizing 5-methylcytosine. They are expressed during development and are essential for mouse gastrulation. However, their postgastrulation functions are not well established. We find that global or endothelial-specific loss of all three Tet enzymes immediately after gastrulation leads to reduced number of hematopoietic stem and progenitor cells (HSPCs) and lethality in mid-gestation mouse embryos. This is due to defects in specification of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 64 publications
3
7
0
Order By: Relevance
“…Tet -TKO embryos displayed pronounced lineage biases, in particular a disruption of primitive erythropoiesis. This is consistent with recent work that found that loss of all three Tet enzymes immediately after gastrulation display severe defects in the specification of haematopoietic stem and progenitor cells [ 46 ]. Using single-cell multi-omics technologies, we find that primitive erythrocytes are associated with global methylation loss, independent of TET enzymes, likely mirroring the demethylation that occurs later in development during definitive erythropoiesis [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Tet -TKO embryos displayed pronounced lineage biases, in particular a disruption of primitive erythropoiesis. This is consistent with recent work that found that loss of all three Tet enzymes immediately after gastrulation display severe defects in the specification of haematopoietic stem and progenitor cells [ 46 ]. Using single-cell multi-omics technologies, we find that primitive erythrocytes are associated with global methylation loss, independent of TET enzymes, likely mirroring the demethylation that occurs later in development during definitive erythropoiesis [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…5c) . These results are consistent with recent chimaera studies 37,38 showing that a lack of TET enzyme activity impairs erythropoiesis.…”
Section: Resultssupporting
confidence: 93%
“…Dnmt1 or Dnmt 3b knockout embryos and Tet TKO embryos die shortly after gastrulation with severe but poorly characterised defects including abnormal primitive streak patterning and differentiation of mesodermal tissues 2729 . Mutations in both Dnmt and Tet genes have been observed frequently in haematological malignancies and clonal hematopoiesis 3036 , and more recently lineage specific knockouts and chimeric mice have demonstrated that TET enzymes are required for efficient hematopoiesis 37,38 , suggesting an important role for methylation and oxidation in this lineage. Bulk RNA-sequencing and whole genome bisulfite-sequencing (WGBS) of Tet TKO embryos implicated Lefty1/2 hypermethylation and perturbed NODAL and WNT signalling as a driver of these defects 28,39,40 , but the broader effect of TET activity loss on the histone modification landscape and enhancer activity was not investigated, despite enhancers being primary regions of DNAme turnover.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, all 3 Tets are expressed in early hematogenic tissues. Tet2 and Tet3 levels are induced during E7.5-E11.5 embryonic development, while Tet1 expression is maintained at similar levels [52]. Combined loss of Tet1 and Tet2 does not impair embryonic hematopoiesis [53].…”
Section: The Role Of Tet Proteins In Early Hematopoietic Generation I...mentioning
confidence: 99%
“…Mice with combined loss of all 3 Tets are early embryonic lethal (E7.5-E8.5) due to defects in gastrulation [55]. To study the role of Tets in embryonic hematopoiesis, Ma et al [52] generated mice with inducible loss of all 3 Tets. Induced deletion of all 3 Tets either globally or endothelial-specifically after gastrulation (E6.5-7.5) leads to reduced numbers of HSPCs and lethality at E11.5-E12.5 due to defects in the transition of ECs to HSPCs.…”
Section: The Role Of Tet Proteins In Early Hematopoietic Generation I...mentioning
confidence: 99%